Economic Potential of the Railway Engineering Industry of Ukraine in the Context of Post-War Recovery and European Integration - Ruban, M.; Chebotarov, Ie. (Економічний вісник Донбасу, 2023)
The study of the set of problems of Ukraine’s post-war restoration and derivative issues of the state’s European integration course involves, first of all, substantiation of the optimal strategic directions of the relevant restoration policy. Generalization of the world experience in the development and implementation of post-war restoration policy serves as an epistemological and scientific-practical basis for the following strategic directions of Ukraine’s restoration: the creation of a transport and logistics cluster based on the expansion of the international alliance – the Lublin Triangle cooperation platform. Expansion of the Lublin Triangle provided that Ukraine takes the necessary measures, is quite realistic by adding to Poland, Lithuania, and Ukraine the Czech Republic, Romania, Moldova, Bulgaria (later, perhaps, also Slovakia, Georgia, and Azerbaijan). In the article, the authors elaborate on their idea, which is substantiated in the Ukrainian and foreign scientific literature, to create the mentioned transport and logistics cluster using a network of transport logistics hubs in the context of the proposed expansion of the Lublin Triangle. Another new historic chance for Ukraine in this area (and in a broader institutional and economic sense) may be the expected invitation to join Germany, France, and Poland in the Weimar Triangle alliance. Based on the analysis of the economic, scientific, and technical state of domestic railway engineering enterprises, the problems and prospects of their wide cooperation with enterprises of Poland, the Baltic States, the Czech Republic, Germany, and France in the sub-sectors of production of locomotives and rolling stock, wagons and special equipment are considered. The appropriate regulatory regime that can ensure the practical implementation of the proposed cooperation (as well as in the broader context of the practical implementation of Ukraine’s post-war restoration policy) should be the creation of a network of special economic zones.